A Project Report on Electronic Customer Relationship Management - TOBIN THOMAS, VARGHESE ABRAHAM, ANISH VARGHESE KOSHY and JOYY JOHN ALPHONSO (2003)
INTERNAL GUIDE: RAJARAJESHWARI, MVJCE EXTERNAL GUIDE: SUDIP, DIGINET
Keywords: Electronic Customer Relationship Management